2015
DOI: 10.1128/mcb.00344-15
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning of the RIG-I-Like Receptor/Interferon Regulatory Factor 3-Dependent Antiviral Innate Immune Response by the Glycogen Synthase Kinase 3/β-Catenin Pathway

Abstract: Induction of an antiviral innate immune response relies on pattern recognition receptors, including retinoic acid-inducible gene 1-like receptors (RLR), to detect invading pathogens, resulting in the activation of multiple latent transcription factors, including interferon regulatory factor 3 (IRF3). Upon sensing of viral RNA and DNA, IRF3 is phosphorylated and recruits coactivators to induce type I interferons (IFNs) and selected sets of IRF3-regulated IFN-stimulated genes (ISGs) such as those for ISG54 (Ifit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 86 publications
1
25
0
Order By: Relevance
“…Since the transcriptional factor IRF3 is a pivotal molecule to facilitate the induction of IFN-β in RLR pathway [19]. Consistently, over-expression of ZWINT markedly increases the abundance of Sendai virus-triggered IRF3 dimerization ( Figure 2E).…”
Section: Zwint Not Only Enhances Sendai Virus-induced But Also Enhancsupporting
confidence: 57%
“…Since the transcriptional factor IRF3 is a pivotal molecule to facilitate the induction of IFN-β in RLR pathway [19]. Consistently, over-expression of ZWINT markedly increases the abundance of Sendai virus-triggered IRF3 dimerization ( Figure 2E).…”
Section: Zwint Not Only Enhances Sendai Virus-induced But Also Enhancsupporting
confidence: 57%
“…GSK3B has been shown before to be an important player in IAV entry (53). Recently, it was shown that GSK3B activation is needed for the expression of IRF3-regulated IFN-stimulated genes (54). The KEA analysis results included substrates of several members of the MAPK family (p38␣, JNK2, ERK1, JNK1, ERK2, MAPKAPK5, MAPK10, MAPK11, and MAPK13) as highly enriched after infection.…”
Section: Phosphoproteomic Analysis Of Influenza Infectionmentioning
confidence: 99%
“…In support of this, we showed that the deletion of the phosphodegron motif of β-catenin decreases the DNA binding activity of IRF3 and the antiviral innate immune response following SeV and VSV infections. The phosphorylation of glycogen synthase at Ser641 following SeV infection and the increase in the phosphotransferase activity of GSK-3 observed through immunocomplex in vitro kinase assays have been additional observations demonstrating an increase in the catalytic activity of GSK-3 towards its substrates [74]. Interestingly, in addition to SeV and VSV, the activation of GSK-3 has previously been reported during infection with coxsackievirus, an RNA virus [103], as well as in response to the HIV-1 Tat protein [104].…”
Section: Cytosolic Rna Sensorsmentioning
confidence: 88%
“…Due to the paucity of these studies, the working models have sometimes been in contradiction. However, pictures are emerging where (1) GSK-3 operates at the level of β-catenin [74] and/or TBK1 [75,76]; and (2) β-catenin acts via the classical holocomplex formed by IRF3 and CBP/p300 [74,[77][78][79][80][81] or TCF [82] to regulate the production of type I IFNs (Figure 3). receptor-associated factors (TRAFs) to polymerized MAVS results in the activation of the constitutively expressed protein kinase TANK-binding kinase 1 (TBK1) and its inducible homologue IKKi (or IKKε).…”
Section: Cytosolic Rna Sensorsmentioning
confidence: 99%
See 1 more Smart Citation